Plasmonic Sensor Based on Multi Fano Resonance in Inverse T Shape Structure for Detection of CO2 Concentration - Lili Zeng; Boxun Li; Ruquan Wen; Xingjiao Zhang (IEEE Photonics Journal)
An inverse T shape structure, consisting of two perpendicular cavities coupled with a bus-waveguide truncated by a block, has been proposed and investigated numerically. Multi Fano resonance, attributing to the interaction of one continuous and two discrete states, can be observed in transmission spectrum. The numerical results are demonstrated by the coupled mode theory. At the same time, it is feasible to produce multi Fano resonance which derive from the splitting of different order modes by adjusting D value, which has been well explained theoretically. When the inverse T shape is filled with Polyhexamethylene biguanide (PHMB), a perfect absorbing coating to monitor the CO2 concentration, the structure can be served as a high sensitivity CO2 detector, whose sensitivity can up to 303 pm/ppm. In addition, the sensitivity of this proposed structure is ∼2.23 times higher than the previous work. The proposed structure has the advantages of simple, compact and easy fabrication. The results represented in this study may have potential applications in sensing and CO2 detector, which can provide the guideline to design other types of gas detector.